IMPLEMENTATION OF BLENDED LEARNING MODEL IN IMPROVING LEARNING OUTCOMES OF WRITING SKILLS - Wisnu Nugroho Aji (Fakultas Bahasa dan Seni UNP, 2022)
This research uses a quasi-experimental design model with the type of equivalent time series. This research aims to describe the application of the blended learning model in learning writting skills, so that learning outcomes and student responses can be known. The research sample are 25 students from the S1 Indonesian Language and Literature Education in academic year of 2020 by a purposive sampling method. The results of student responses as a whole, students feel very enthusiastic with the implementation of the blended learning model and enjoy the learning process. There are 90% of students stated that they were interested and liked the blended learning model. The results showed that the average students’ learning outcomes at each stage always increased. Stage 1 is 75,20 (B) and stage 2 is 92.30 (A). The increase in learning outcomes is evidenced by the average n-gain value in stage 2, which is 0.92 (high criteria). The conclusion of the research is that students' interest, motivation, and learning awareness increase after the blended learning model is applied to writting skills courses.